Analysis on Impact of Emotional Psychology Appeal towards the Employee Performance - S., Arun Kumar; A. , Celina; K. , Sankara Moorthy (International Journal of Psychosocial Rehabilitation, 2020)
In order to have better performance from employees in an organization, it is significant to understand the needs of the employees. There are physical rewards as well as intangible benefits for the employees. Organizations that better understand the emotional quotient of the employees will help them deliver the expected performance . This paper deals with the constructs that influence the emotional intelligence in an organization.